2021
DOI: 10.1055/a-1322-3205
|View full text |Cite
|
Sign up to set email alerts
|

Stress und Covid-19: Ein Narrativer Review über neuroendokrin-immune Mechanismen, die eine Abwehr von SARS-CoV-2 verbessern könnten

Abstract: Zusammenfassung Ziel des Reviews Die COVID-19 Pandemie ist auf dem Vormarsch, die Sorgen und Ängste in der Bevölkerung wachsen, ebenso wie im medizinischen System. Aus der Perspektive der Stressforschung steht jetzt auf der einen Seite die Frage, wie diese psychosozialen Belastungen bewältigt werden können. Auf der anderen Seite entsteht die Frage, ob bestimmte Formen von Stress zu einer Häufung von In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 109 publications
(77 reference statements)
0
3
0
2
Order By: Relevance
“…Protracted systemic inflammation is an important pathogenetic factor in depressive-anxious disorders during COVID-19 convalescence (7,10,24,3032). Stress being the key co-variate of poor mental health in the study collectives was proposed to modulate anti-SARS-CoV-2 immunity culminating in more severe COVID-19 (33) and to perpetuate the systemic low-grade inflammation(28,33). Other possible mechanisms include direct viral infection of the central nervous system, neuroinflammation, microvascular thrombosis and neurodegeneration(34).…”
Section: Discussionmentioning
confidence: 99%
“…Protracted systemic inflammation is an important pathogenetic factor in depressive-anxious disorders during COVID-19 convalescence (7,10,24,3032). Stress being the key co-variate of poor mental health in the study collectives was proposed to modulate anti-SARS-CoV-2 immunity culminating in more severe COVID-19 (33) and to perpetuate the systemic low-grade inflammation(28,33). Other possible mechanisms include direct viral infection of the central nervous system, neuroinflammation, microvascular thrombosis and neurodegeneration(34).…”
Section: Discussionmentioning
confidence: 99%
“…Es ist außerdem hinreichend belegt, dass psychische und psychosomatische Vorerkrankungen Vulnerabilitätsfaktoren für das Auftreten von psychischen Long-/Post-COVID-Symptomen darstellen. Zudem legen psychoneuroimmunologische Konzepte nahe, dass insbesondere Stress zur Verschlechterung und Chronifizierung von inflammatorischen Erkrankungen beitragen kann 279 . Auch wurden Zusammenhänge zwischen initial schwacher Immunabwehr und langfristig erhöhten Inflammationsparametern mit Fatigue berichtet 173 .…”
Section: Psychische Aspekteunclassified
“…Rehabilitation angezeigt. Zentral ist die multimodale Behandlung der Patienten 279 324 . Dies schließt auch die Einbindung von Bewegungsangebotenangeboten 325 , Selbsthilfe-Gruppen (z.…”
Section: Psychische Aspekteunclassified
“…Neuroendocrineimmune mechanisms might boost the risk of a SARS-CoV-2 infection and have a negative impact on the course of the following coronavirus disease . However, epidemiological data on the hypothesized interplay between emotional distress and an infection with SARS-CoV-2 are largely missing (Peters et al, 2021). Experimental studies have revealed that pre-existing emotional burden, such as stress or the feeling of loneliness, entails a risk of viral infection and may negatively impact the course of infectious diseases (Cohen et al, 1991;Cole et al, 2011;Cohen et al, 2015;LeRoy et al, 2017;Cohen, 2021).…”
Section: Introductionmentioning
confidence: 99%